2022
DOI: 10.18203/2320-6012.ijrms20223086
|View full text |Cite
|
Sign up to set email alerts
|

A study of bone marrow angiogenesis and its correlation with serum vascular endothelial growth factor levels in acute leukaemia

Abstract: Background: Angiogenesis, which is the development of new capillaries from existing blood vessels, occurs in both the developing embryo and postnatal life. The growth of solid tumours requires the development of micro vessels; therefore, tumour expansion correlates with the extent of angiogenesis.Methods: A prospective study was conducted on bone marrow trephine biopsies of 40 new cases of acute leukaemia diagnosed on complete blood count, bone marrow aspiration examination, and flow cytometry, including 20 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Presence of higher level of microvessels density has proved its association with the pathogenesis of leukaemia. 29 Chemotherapeutic drugs exert their anti-angiogenic effects possibly by impairing the growth and function of microenvironmental cells and promoting apoptosis of endothelial cells. 30 Recent study revealed significant reduction of bone marrow MVD in completely recovered patients from acute myeloid leukaemia following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Presence of higher level of microvessels density has proved its association with the pathogenesis of leukaemia. 29 Chemotherapeutic drugs exert their anti-angiogenic effects possibly by impairing the growth and function of microenvironmental cells and promoting apoptosis of endothelial cells. 30 Recent study revealed significant reduction of bone marrow MVD in completely recovered patients from acute myeloid leukaemia following chemotherapy.…”
Section: Discussionmentioning
confidence: 99%